A Sustainable Approach In Advancement Of Earth Sciences & Foundation Engineering Towards Green Construction. Issue 1 (1st February 2023) - Urvashi
Abstract: The goal of this study was to look into the aspects that influence green building project management and to figure out what factors contribute to the best results. The inquiry was intended to look into the characteristics that contribute to project success in green building. Questionnaires were gathered from environmental people, construction personnel, and legal personnel groups, all of whom were involved in the administration of green building projects. Staff factors, material elements, monetary variables, administrative variables, and eco-productivity factors were all examined and variables were prioritized using the Relative Importance Index (RII). After a thorough analysis of the factors that influence the management of green development projects, the findings were divided into five categories for the first and second most essential variables. For the labour force perspective, disposition toward the project and task comprehension were two independent driving factors. Productivity and cost were the main drivers from a material standpoint. The cost increase and change in development were the driving drivers from a monetary standpoint. From an administrative standpoint, the driving factors were the related document, the endorsement cycle, and the government's recognition of venture members. This paper shows the material reuse capacity increase and decrease in assets utilization which were the driving elements in this work, focused on eco-effectiveness.